Analisis Pengaruh Kinerja Keuangan dalam Memprediksi Financial Distress pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Mawarda, Aisa Senta; Enny Susilowati Mardjono; Ira Septriana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The aim of this study is to analyze the impact of financial performance in predicting financial distress in banking companies listed on the Indonesia Stock Exchange from 2019 to 2023. This study examines 46 banking companies registered on the Indonesia Stock Exchange during the period. The sample consists of 28 companies selected using purposive sampling. Data analysis is conducted using multiple linear regression.